The Correlation Between Exposure to English-Language Content on Instagram and Listening Comprehension among EFL Students at UIN Datokarama Palu - Miftahul Inayah; Ruslin Ruslin; Hijrah Syam; Nur Asmawati; Zulaini rengur (MASI Mandiri Edukasi, 2026)
Listening comprehension is a foundational receptive skill in English as a Foreign Language (EFL) learning, yet learners often face challenges due to limited access to authentic spoken English. With the widespread use of social media, platforms like Instagram provide abundant daily exposure to authentic audio-visual English content. Although previous studies have explored Instagram in language learning, most have focused on qualitative perceptions or formal classroom-based interventions, leaving the correlation between informal, self-initiated exposure to spoken Instagram content and objective listening comprehension underexplored in higher education contexts. This study examines the correlation between exposure to Instagram English content and listening comprehension among university-level EFL students at UIN Datokarama Palu. Employing a quantitative correlational design, the study involved 38 EFL students selected through total sampling. Data were gathered using a 20-item Instagram English Content Exposure questionnaire and a 10-item listening comprehension test, and analyzed using descriptive statistics and Pearson Product-Moment correlation after confirming normality and linearity assumptions. Based on standard categorization, participants demonstrated a high level of exposure to Instagram English content (M = 79.32, SD = 9.927) and a moderately high level of listening comprehension (M = 74.21, SD = 17.802). Pearson correlation revealed a strong, statistically significant positive relationship between the two variables (r = 0.977, p < 0.001). The findings indicate that higher informal exposure to spoken English content on Instagram is strongly associated with better listening comprehension performance. While the study does not establish causality or test a pedagogical intervention, it offers practical and empirical contributions by highlighting Instagram’s potential as an effective supplementary resource for expanding authentic input and supporting autonomous listening practice in EFL higher education.